27 - 3^3 + 4 * 2^2 - 6 can be simplified as follows:
27 - 3^3 + 4 * 2^2 - 6
= 27 - 27 + 4 * 4 - 6
= 0 + 16 - 6
= 16 - 6
= 10
So the simplified expression is 10.
Simplify: 27−3^3+4⋅2^2−6 .(1 point)
$$
7 answers
Evaluate: a+b^4 where a=2, b=3.(1 point)
$$
$$
To evaluate the expression a + b^4 where a = 2 and b = 3:
a + b^4 = 2 + 3^4 = 2 + 81 = 83
So the value of the expression is 83.
a + b^4 = 2 + 3^4 = 2 + 81 = 83
So the value of the expression is 83.
Simplify: 6÷3⋅2−5+7⋅2 .
To simplify the expression 6 ÷ 3 ⋅ 2 - 5 + 7 ⋅ 2, we follow the order of operations, which is also known as PEMDAS (parentheses, exponents, multiplication and division, and addition and subtraction) to simplify it step by step:
6 ÷ 3 ⋅ 2 - 5 + 7 ⋅ 2
= (6 ÷ 3) ⋅ 2 - 5 + 7 ⋅ 2
= (2) ⋅ 2 - 5 + 7 ⋅ 2
= 4 - 5 + 7 ⋅ 2
= 4 - 5 + 14
= -1 + 14
= 13
So, the simplified result is 13.
6 ÷ 3 ⋅ 2 - 5 + 7 ⋅ 2
= (6 ÷ 3) ⋅ 2 - 5 + 7 ⋅ 2
= (2) ⋅ 2 - 5 + 7 ⋅ 2
= 4 - 5 + 7 ⋅ 2
= 4 - 5 + 14
= -1 + 14
= 13
So, the simplified result is 13.
Simplify: 18−2⋅3+6^2/2 .(1 point)
To simplify the expression 18 - 2 * 3 + 6^2 / 2, we again follow the order of operations (PEMDAS):
First, perform the exponentiation:
6^2 = 36
Next, perform the multiplication and division from left to right:
18 - 2 * 3 + 36 / 2
= 18 - 6 + 36 / 2
= 18 - 6 + 18
Finally, perform the addition and subtraction from left to right:
18 - 6 + 18
= 12 + 18
= 30
So, the simplified result is 30.
First, perform the exponentiation:
6^2 = 36
Next, perform the multiplication and division from left to right:
18 - 2 * 3 + 36 / 2
= 18 - 6 + 36 / 2
= 18 - 6 + 18
Finally, perform the addition and subtraction from left to right:
18 - 6 + 18
= 12 + 18
= 30
So, the simplified result is 30.